Large-Eddy Simulation of Premixed Combustion in the Corrugated-Flamelet Regime. Issue 9 (1st September 2016) - Langella, I.; Swaminathan, N.; Williams, F. A.; Furukawa, J.
ABSTRACT: Large-eddy simulation (LES) is applied to a fuel-lean turbulent propane-air Bunsen flame in the corrugated-flamelet regime. The subgrid-scale (SGS) modeling includes a previously developed treatment of the total enthalpy along with three different SGS velocity, , models. In addressing the filtered reaction rate, a presumed probability density function (PDF) approach is employed for the reaction-progress variable, closed by a transport equation for its SGS variance. The statistics obtained using the three models are in good agreement with the measurements and do not differ significantly from each other for first-order moments suggesting that commonly used SGS modeling may be adequate to get the mean velocities and reaction progress variable. However, all three SGS velocity models fail to reflect a measured bimodality of the PDF of the radial component of the velocity in the central portion of the flame. This emphasizes a need for further development of models required at the reaction rate closure level for practical LES of combustion in the corrugated-flamelet regime.